The Molybdenum Storage Protein: A soluble ATP hydrolysis‐dependent molybdate pump. (12th November 2018) - Poppe, Juliane; Brünle, Steffen; Hail, Ron; Wiesemann, Katharina; Schneider, Klaus; Ermler, Ulrich
Abstract : A continuous FeMo cofactor supply for nitrogenase maturation is ensured in Azotobacter vinelandii by developing a cage‐like molybdenum storage protein (MoSto) capable to store ca. 120 molybdate molecules ( MoO 4 2 − ) as discrete polyoxometalate (POM) clusters. To gain mechanistic insight into this process, MoSto was characterized by Mo and ATP/ADP content, structural, and kinetic analysis. We defined three functionally relevant states specified by the presence of both ATP/ADP and POM clusters (MoStofunct ), of only ATP/ADP (MoStobasal ) and of neither ATP/ADP nor POM clusters (MoStozero ), respectively. POM clusters are only produced when ATP is hydrolyzed to ADP and phosphate. V max was ca. 13 μmolphosphate ·min −1 ·mg −1 and K m for molybdate and ATP/Mg 2+ in the low micromolar range. ATP hydrolysis presumably proceeds at subunit α, inferred from a highly occupied α‐ATP/Mg 2+ and a weaker occupied β‐ATP/no Mg 2+ ‐binding site found in the MoStofunct structure. Several findings indicate that POM cluster storage is separated into a rapid ATP hydrolysis‐dependent molybdate transport across the protein cage wall and a slow molybdate assembly induced by combined auto‐catalytic and protein‐driven processes. The cage interior, the location of the POM cluster depot, is locked in all three states and thus not rapidly accessible for molybdate from the outside. Based on V max, the entire Mo storage process should be completed in less than 10 s but requires, according to the molybdate content analysis, ca. 15 min. Long‐time incubation of MoStobasal with nonphysiological high molybdate amounts implicates an equilibrium in and outside the cage and POM cluster self‐formation without ATP hydrolysis. Databases: The crystal structures MoSto in the MoSto‐F6, MoSto‐F7, MoStobasal, MoStozero, and MoSto‐F1vitro states were deposited to PDB under the accession numbers PDB6GU5, 6GUJ, 6GWB, 6GWV, and6GX4 . Abstract : Polyoxomolybdate cluster storage of the molybdenum storage protein is separated into a rapid ATP hydrolysis‐dependent molybdate transport across the proteinous cage wall and a slow protein‐promoted and ATP‐independent molybdate self‐assembly process. Polyoxomolybdate clusters are formed in specific protein pockets supported by the high molybdate concentrations accumulated inside the cage provided via the molybdate pump.